Fifteen-Year Trends in Coronary Risk Factors in Finland, with Special Reference to North Karelia - VARTIAINEN, ERKKI; KORHONEN, HEIKKI J; PIETINEN, PIRJO; TUOMILEHTO, JAAKKO; KARTOVAARA, LEENA; NISSINEN, AULIKKI; PUSKA, PEKKA (International Journal of Epidemiology, 1991)
The North Karelia Project, a major demonstration programme for coronary heart disease (CHD) prevention, was begun in an eastern province of Finland in 1972. A number of national CHD prevention activities have been undertaken, quite a few of them since 1977. This paper reports the 15-year changes in CHD risk factors (serum cholesterol, blood pressure, and smoking) in North Karelia and in the original reference area of the project, and more recent changes in a third area in southwestern Finland. The results are based on well-standardized, comparable surveys of cross-sectional populations, aged 30 to 59 years. The results indicate that risk factors reduced markedly in North Karelia from 1972–1977, to a lesser extent from 1977–1982, and only a little from 1982–1987. There was also a decline in the reference area during the first ten years (1972–1982) but the changes did not exceed those in North Karelia and during the second phase, from 1982–1987, risk factor changes were minor. Risk factor levels in the third area in southwestern Finland changed little from 1982–1987. Present serum cholesterol and blood pressure levels in North Karelia are still higher than in southwestern Finland, but smoking is less common among North Karelian men. These findings are discussed in the light of the recent information on Finnish dietary changes and CHD mortality; their bearing on the need for new cardiovascular disease prevention activities in Finland is also discussed.